2020
DOI: 10.1108/jfmpc-08-2019-0067
|View full text |Cite
|
Sign up to set email alerts
|

Does family ownership affect the profitability of construction and real estate firms? Evidence from India

Abstract: Purpose The study aims to find if family-owned construction and real estate firms in India are more profitable compared to non-family-owned construction and real estate firms. The study also examines if family ownership and institutional ownership are drivers of the firm profitability. Design/methodology/approach The study uses data of 199 construction and real estate firms listed on the National Stock Exchange (NSE), India. The data pertains to a period of 13 years (2006-2018). The family firm is defined on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Where the diagnostic analysis reported that the models of the current study show heteroscedasticity and autocorrelation, it needs to address this issue to achieve accurate estimates. FGLS is one of the critical techniques (Parks, 1967); however, this technique is invalid when N is greater than T; it requires a relatively large T in relation to N. Thus, the current study employs (PCSE), because it is a suitable estimator when N is greater than T (Carl et al, 2020;Singla, 2020;Mnif & Imen, 2020). Furthermore, to mitigate the effect of outliers, every variable that has extreme values at the upper and lower of 1 and 5% has been winorized.…”
Section: Research Modelmentioning
confidence: 99%
“…Where the diagnostic analysis reported that the models of the current study show heteroscedasticity and autocorrelation, it needs to address this issue to achieve accurate estimates. FGLS is one of the critical techniques (Parks, 1967); however, this technique is invalid when N is greater than T; it requires a relatively large T in relation to N. Thus, the current study employs (PCSE), because it is a suitable estimator when N is greater than T (Carl et al, 2020;Singla, 2020;Mnif & Imen, 2020). Furthermore, to mitigate the effect of outliers, every variable that has extreme values at the upper and lower of 1 and 5% has been winorized.…”
Section: Research Modelmentioning
confidence: 99%
“…Running the model before addressing these issues leads to biased results. Therefore, to overcome these econometric problems, the current study used panel corrected standard errors (PCSE), which is a suitable estimator that adjusts both autocorrelation and heteroscedasticity (Singla, 2020;Mnif & Imen, 2020;Carl et al, 2020). As noted, the following model is estimated by the panel corrected standard errors (PCSE).…”
Section: Research Modelmentioning
confidence: 99%
“…The results indicated that heteroscedasticity and autocorrelation are present. To overcome these econometric problems, the present study uses panel corrected standard errors (PCSE) which is a suitable estimator that adjusts autocorrelation, heteroscedasticity, and cross-section dependence (Singla, 2020;Mnif & Imen, 2020;Carl et al, 2020). Table VI showed that there is a significant positive relationship between board size and CSR disclosure where (Coef.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Because the diagnostic test indicated that the model of current study suffer from the contemporaneous correlation across the unit and unit level heteroscedasticity it is necessary to treat this problem to obtain efficient estimates; one first approach is the usage of FGLS (Parks, 1967); however, this method is not valid in situations when N>T because it needs a relative large T in relation to N. In this line, this method is limited to time-series cross-section (TSCS) research. Therefore, the present study uses panel corrected standard errors (PCSE), as it is an appropriate estimator when N>T (Singla, 2020;Mnif & Imen, 2020). In addition, all variables that have extreme values at the top and bottom 1 and 5% to mitigate the influence of outliers have been winsorized.…”
Section: Research Modelmentioning
confidence: 99%
“…The study also performed a normality test to check for the normal distribution of residuals. To overcome these econometric issues, the current study apply panel corrected standard errors (PCSE), where it is an suitable estimate that corrects all of heteroscedasticity ,autocorrelation and cross-section dependence (Singla, 2020;Mnif & Imen, 2020;Carl et al, 2019). Table V presents the outcomes of empirical research of corporate governance on firm performance.…”
Section: Diagnostic Testsmentioning
confidence: 99%